Molecular and morphological characterization of Amathia distans Busk and Amathia brasiliensis Busk (Bryozoa: Ctenostomata) from the tropical and subtropical Western Atlantic - Fehlauer-Ale, Karin H.; Vieira, Leandro M.; Winston, Judith E. (Zootaxa, 2011)
Morphological and molecular analyses have proven to be complementary tools of taxonomic information for the redescription of the ctenostome bryozoans Amathia brasiliensis Busk, 1886 and Amathia distans Busk, 1886. The two species, originally described from material collected by the ‘Challenger’ expedition but synonymized by later authors, now have their status fixed by means of the selection of lectotypes, morphological observations and analyses of DNA sequences described here. The morphological characters allowing the identification of living and/or preserved specimens are (1) A. brasiliensis: whitish-pale pigment spots in the frontal surface of stolons and zooids, and a wide stolon with biserial zooid clusters growing in clockwise and anti-clockwise spirals along it, the spirality direction being maintained from maternal to daughter stolons; and (2) A. distans: bright yellow pigment spots in stolonal and zooidal surfaces including lophophores, and a slender stolon, thickly cuticularized, with biserial zooid clusters growing in clockwise and anti-clockwise spirals along it and the spirality direction not maintained from maternal to daughter stolons. Pairwise comparisons of DNA sequences of the mitochondrial genes cytochrome c oxidase subunit I and large ribosomal RNA subunit revealed deep genetic divergence between A. brasiliensis and A. distans. Finally, analyses of those sequences within a Bayesian phylogenetic context recovered their genealogical species status.